Rapid Electrochemical Synthesis and Solvatochromic Emission Behavior of Single Crystals of a Heteronuclear Platinum(II)‐Copper(I) Complex - Yijia Liu; Limin Zhang; Yun Ma; Pengfei She; Wei Tang; Wai‐Yeung Wong (Aggregate)
ABSTRACT In this study, we present a novel multicomponent self‐assembly approach that offers good potential for crafting heterometallic complexes with exceptional constitutional control. This method generates metal ions from a sacrificial anode by using an electric field, which then coordinates with a metal complex precursor. As a proof‐of‐concept demonstration, we successfully synthesized single crystals of a heterometallic platinum(II)‐copper(I) (Pt[II]‐Cu[I]) complex at an exceptionally rapid rate within 30 s by applying a voltage to an acetonitrile solution of [Pt(ppy)(CN)2]−Bu4N+, using copper foil as the anode. Intriguingly, by finely adjusting the intensity and duration of the electric field, we achieved a variety of supramolecular structures, spanning from spherical to rod‐like and even flower‐like morphologies. Additionally, we found that the photoluminescence property of the resultant crystal can be reversibly shifted among green, orange, and cyan by merely altering the solvent environment. Finally, the crafted heterometallic Pt(II)‐Cu(I) complex has shown great promise in advanced anti‐counterfeiting applications.